Nanoengineering of 2D MBenes for energy storage applications: A review - Akgul, Eda Taga; Altıncı, Osman Cem; Umay, Ahmet; Aghamohammadi, Parya; Farghaly, Ahmed A.; Ma, Pianpian; Chen, Yuanqing; Demir, Muslum (Journal of energy storage, 2024)
2D transition metal borides (MBenes), a flourishing member of the 2D nanomaterial family, show great potential in a number of study areas. MBenes have received increasing attention thanks to their excellent electrical conductivity, structural and mechanical properties, and chemical stability, which have captivated researchers and sparked further exploration. Extensive theoretical and experimental investigations have unveiled its remarkable potential as electrode materials for electrochemical storage applications, making MBenes a subject of great interest. Despite the growing interest and numerous studies conducted, there is a lack of a comprehensive and systematic appraisal of MBenes' applications in electrochemical energy storage systems. In light of this, firstly, we provide an overview of the current progress in the fabrication and characterization of MAB phases and MBenes. For the synthesis of MBenes, the following fabrication techniques were discussed; liquid-phase exfoliation, solid-state mechanical exfoliation, chemical vapor deposition, high-pressure chemical vapor deposition, microwave-assisted chemical etching, and ultrasound-assisted chemical etching methods. Then, we delve into the captivating potential of MBenes, specifically in the realm of energy storage applications and their role in enhancing electrochemical storage capabilities. The discussion encompasses their application in lithium-ion, lithium‑sulfur, and lithium-selenide batteries, supercapacitors and other energy storage systems, providing a comprehensive perspective on their contributions to the energy landscape. Finally, a brief but significant summary of the challenges and opportunities of MBenes in practical applications was summarized. The present review provides a guide and scientific motivation for creating and developing advanced MBene-based nanomaterials, addressing the growing demand for cutting-edge energy storage systems. •2D MBene nanostructures have been reviewed for energy storage technology application.•The challenges and opportunities of MBenes in practical implementations was summarized.•The assembled supercapacitor exhibits excellent electrochemical properties.•The role of MBene in composites were elucidated.